History of the Development of Mażhab, Fiqh and Uṣūl Al-Fiqh: Reasoning Methodology in Islamic Law - Anshori, Ahmad Yani; Abdurrahman, Landy Trisna (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This research explores the historical evolution and significance of Uṣūl Al-Fiqh (the principles of Islamic jurisprudence) and its continued relevance in contemporary Islamic scholarship. Beginning in the second century A.H. (8th century CE), jurists developed legal rulings from the Qur'an and Sunnah using methods such as analogy (qiyās) and juristic preference (istiḥsān), ensuring flexibility and justice within Islamic law. The formalization of Uṣūl Al-Fiqh as a distinct science commenced with Imam al-Shafi'i in the early 9th century CE, whose systematic documentation in al-Risalah profoundly influenced subsequent Islamic legal theory. The methodologies developed within Uṣūl Al-Fiqh, including qiyās and ijmā’, remain vital for interpreting and applying Sharia principles today. This research employs a historical approach, analyzing primary sources and scholarly works both theoretically and empirically, to trace the development and application of Uṣūl Al-Fiqh across various Islamic legal schools. The findings highlight the crucial role of Uṣūl Al-Fiqh in maintaining the continuity and adaptability of Islamic law, emphasizing that its methodologies continue to offer valuable solutions to contemporary legal, ethical, and social challenges. Furthermore, this study reveals how the dynamic and evolving nature of Islamic legal reasoning ensures the continued relevance of Islamic law in addressing modern issues. Future research should focus on finding solutions to emerging challenges in Islamic jurisprudence and developing innovative methodologies to address the ongoing evolution of Islamic legal thought.